Transcatheter mitral valve replacement (TMVR) for degenerated mitral valve bioprosthesis - A case series - Viveka Kumar; Mitendra Singh Yadav; Sangeeta Dhir (IHJ Cardiovascular Case Reports, 2023)
Mitral regurgitation (MR) is the leading cause of heart valve disease worldwide. In aging population, the incidence of mitral regurgitation (MR) has gradually surpassed that of aortic valve stenosis. We present a report of 5 cases,with history of rheumatic heart disease and old malfunction bioprosthetic valve, presenting with dyspnea, poor ejection fraction.Investigations revealed severe mitral stenosis and regurgitation. TMVR (trans catheter mitral valve replacement) was done with successful outcome.